Management Control System and Firm Performance in Nepalese Commercial Bank - Upadhyay, Jitendra Prasad; Singh, Sanju Kumar; Panthi, Suresh (Ekonomi dan Bisnis, 2024)
This study focused on the interplay of control levers and organizational learning as well as the impact of Management Control Systems (MCS) on firm performance in Nepalese Commercial Banks. The study aims to examine the relationships between MCS levers (belief, boundary, diagnostic, interactive) and firm performance and assess the mediating role of organizational learning in this relationship. The study was done using descriptive and causal-comparative design, where a survey was carried out by deriving the responses from the employees of various commercial banks in Kathmandu. The findings of the study highlighted the significant correlations between MCS, organizational learning, and performance, highlighting MCS as a key tool for enhancing performance in the Banking sector. This study acknowledges limitations such as focusing only on Kathmandu and suggests future research to expand geographically and explore other sectors for broader applicability. Keywords: Management Control Systems, Levers of Control, Organizational Learning, Banking Sector.e other sectors for broader applicability.